SIKAP PRESIDEN RODRIGO DUTERTE ATAS PUTUSAN PERMANENT COURT OF ARBITRATION (PCA) TENTANG SENGKETA LAUT CHINA SELATAN ANTARA FILIPINA DAN TIONGKOK - Ferdinandsyah, Arie (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This research analyzes the stance of the President of the Philippines, Rodrigo Duterte on the arbitral award of the Permanent Court of Arbitration (PCA) that ruled in favour of the Philippines over China in 2016, based on the United Nations Convention on the Law of the Sea (UNCLOS). The main issue of this research is about why Duterte refused to implement the PCA arbitral award on the South China Sea dispute between the Philippines and China, relations between Duterte's government with countries and regional organizations that have interests in the South China Sea, and its implications for the dispute in the region. Results of this research find that the personality and political style of Duterte have a significant influence on his stance to the PCA arbitral award on the South China Sea dispute. Emotional beliefs and his pragmatic stance made Duterte cultivate an accommodating relationship to the economic interests of China to gain economic benefits for the Philippines. Duterte's personality and political style enable him to change his stance on the PCA award and China when the benefits of the cooperation did not deliver as expected. Hence, this research underscores that individual factors play a significant role in shaping the foreign policy of Duterte to the PCA arbitral award on the South China Sea dispute with China. Keywords: Rodrigo Duterte, PCA, South China Sea, UNCLOS